2003
DOI: 10.1104/pp.102.019281
|View full text |Cite
|
Sign up to set email alerts
|

Light Stress-Induced One-Helix Protein of the Chlorophylla/b-Binding Family Associated with Photosystem I

Abstract: The superfamily of light-harvesting chlorophyll a/b-binding (Lhc) proteins in higher plants and green algae is composed of more than 20 different antenna proteins associated either with photosystem I (PSI) or photosystem II (PSII). Several distant relatives of this family with conserved chlorophyll-binding residues and proposed photoprotective functions are induced transiently under various stress conditions. Whereas "classical" Lhc proteins contain three-transmembrane ␣-helices, their distant relatives span t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
78
3
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(88 citation statements)
references
References 44 publications
6
78
3
1
Order By: Relevance
“…The specific interaction of ScpDHis with PSII was further confirmed by the observation that in the absence of PSII, the ScpDHis protein was present in the form of small protein complexes. This also indicated that ScpDHis does not interact with other large thylakoid membrane complexes, particularly PSI, as was shown recently for the plant SCP homologue OHP (36). We also succeeded in a more detailed localization of ScpDHis within PSII as we detected the protein in the complex of CP47 and PsbH that accumulates at low levels in the strain unable to assemble PSII complexes because of the missing cytochrome b 559 (Fig.…”
Section: Discussionsupporting
confidence: 79%
“…The specific interaction of ScpDHis with PSII was further confirmed by the observation that in the absence of PSII, the ScpDHis protein was present in the form of small protein complexes. This also indicated that ScpDHis does not interact with other large thylakoid membrane complexes, particularly PSI, as was shown recently for the plant SCP homologue OHP (36). We also succeeded in a more detailed localization of ScpDHis within PSII as we detected the protein in the complex of CP47 and PsbH that accumulates at low levels in the strain unable to assemble PSII complexes because of the missing cytochrome b 559 (Fig.…”
Section: Discussionsupporting
confidence: 79%
“…When the Arabidopsis genome sequence appeared, it was apparent that two of the proposed Lhcb2 genes (Jansson, 1999) were actually two alleles of the same gene, resulting in renaming the Lhcb2.4 (At3g27690) gene to Lhcb2.3 (Legen et al, 2001;Andersson et al, 2003a). On the other hand, a gene coding for an additional OHP that initially escaped detection was subsequently characterized (Andersson et al, 2003b), keeping the number of known genes at 30 in Arabidopsis. In poplar the Lhc supergene family is slightly larger with 39 Lhc genes identified (Table I).…”
Section: Resultsmentioning
confidence: 99%
“…The Lhc supergene family of higher plants also contains genes coding for proteins that exhibit sequence similarity to the Lhc proteins, namely, the four-helix protein PsbS and the light-harvesting-like (LIL) proteins. So far, six different classes of Lil genes have been identified (Jansson, 1999;Heddad and Adamska, 2000;Andersson et al, 2003b). The Lil1 genes code for the three-helix early light-inducible proteins (ELIPs), two types of one-helix proteins (OHPs) are encoded by Lil2 (OHP1) and Lil6 (OHP2), and two types of stressenhanced proteins (SEPs) are encoded by Lil4 (SEP1) and Lil5 (SEP2).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…OHP, SEP, and ELIP proteins are proposed to be involved in protection against excessive light. The expression of the genes for these proteins is induced under strong illumination (15)(16)(17)(18)(19). In addition, it has also been suggested that ELIP functions as a repressor of chlorophyll biosynthesis (20).…”
mentioning
confidence: 99%